Modelling complexity in retail supply chains. Issue 2 (1st February 2016) - Ekinci, Esra; Baykasoglu, Adil
Abstract : Purpose: – The purpose of this paper is to describe the characteristics of complexity and how a retail supply chain can contain complexity in itself. A case has been provided to show the measurement of complexity with/without information sharing and the relation of complexity with the performance measures. Quantification of the complexity will help the practitioners to take strategic actions. Design/methodology/approach: – System dynamics simulation has been used to model the retail supply chain with and without information sharing and data visibility. Entropy-based metric used for quantification and comparison of complexity based on the outputs of the models. Performance measures proposed for the retail supply chains to understand the effect of data visibility. Findings: – Paper provides insight about the complexity of retail supply chain perspective. Using system dynamics modelling can be a useful way to perform what-if type analysis before business process changes. Including both complexity and performance measures can be useful to understand if the complexity is good or bad for the business and if it is in manageable amount. Research limitations/implications: – Paper can encourage the future research on retail supply chains. Practical implications: – Approach can be useful to analyse what-if type analysis in practice easily. It can support strategic decision making process. Originality/value: – Combines retail supply chain with complexity and performance measurement.